(untitled) (Global Journal of Science Frontier Research, 2025)
The article reveals that if the builders of the pyramids knew about Pi the golden ratio and the speed of light they must have had advanced knowledge However this was not enough to convince the Egyptologists that the Pharaohs could not have built the pyramids I hope the new stunning discovery from the latest quantum interpretation of radar scanning would 1 New chambers were found in the pyramids and 2 two-miles-deep constructions were found under the pyramids This raises the question Were the pyramids built by extra-terrestrials and who were these extra-terrestrials This article reveals that the pyramids were built by the Nephilim from the Bible the Fallen Angels who mated with Earthly women But they had to first genetically re-engineer the Earthly women to be able to do so because they were different species This makes the Nephilim who built the pyramids our fathers and our co-creators as species The article even reveals from where they came and who they were